Acute Cholecystitis Presenting as Acute Coronary Syndrome with ST-Segment Depression - Laudari, Shankar; Yadav, Krishna; Dhakal, Abiona; Gurung, Kushal; Pandey, Mahesh; Laudari, Pratikshya (Journal of National Heart and Lung Society Nepal, 2025)
Background: Acute cholecystitis may mimic acute coronary syndrome (ACS), both symptomatically and on electrocardiography (ECG), which can lead to cardiac interventions. While ST-segment elevation in such scenarios has been reported, ST-segment depression is a rarer presentation. Case Summary: A 55-year-old woman with a history of Hypothyroidism presented to the emergency department with central chest pain, epigastric discomfort, dyspnea, and nausea since few days. ECG showed ST depression in infero-anterior leads (II, III, aVF, V1-V6). Cardiac biomarkers (CPK-MB=2.5 ng/mL, Troponin I=0.01 ng/mL) were normal suggestive of Unstable Angina. Coronary angiography revealed only minor coronary artery disease. Abdominal ultrasound confirmed acute calculous cholecystitis. The patient was managed conservatively and planned for cholecystectomy. Patient had gradual resolution of symptoms and dynamic ECG changes (T inversion in infero-anterior leads). This case report has been so far the first case publication from Nepal but very few case reports have been published internationally. Conclusion: This case demonstrates that acute cholecystitis can present with ST-segment depression mimicking ACS. Clinicians should maintain a broad differential diagnosis in patients with chest pain, especially when cardiac workup is inconclusive and gastrointestinal history is relevant.